Ownership succession, risk taking and debt financing from the perspective of the institutional environment. - Yanbo Liu; Hanzhou Liu; Decai Tang; Chenxi Yin; Lin Kong (PLoS ONE, 2025)
This study examines family firms listed on China's A-share market, using a two-way fixed effects model to explore the impact of ownership succession on debt financing and the moderating role of the institutional environment. The findings indicate that second-generation ownership succession reduces risk-taking, which in turn lowers debt financing. Additionally, the institutional environment mitigates the negative relationship between second-generation ownership succession, risk-taking, and debt financing. Further analysis reveals that factors such as the development of the non-state-owned economy, the maturity of factor markets, and advancements in market intermediaries and legal systems significantly moderate these relationships. This study broadens the research perspective on intergenerational succession in family businesses and offers empirical insights to help family firms adapt to regional institutional differences more effectively.